Continuous wound infiltration versus placebo following elective minimally invasive colorectal surgery (CIMICS): study protocol for a randomised controlled trial - Sofie Glazemakers; Stijn H.J. Ketelaers; Harm J. Scholten; Robert-Jan Schipper; Michaël I. Meesters; Jacobus W.A. Burger; Johanne G. Bloemen (PLoS ONE, 2026)
Background Enhanced Recovery After Surgery (ERAS) programs emphasize multimodal analgesia to minimize opioid use and improve patient outcomes. Continuous wound infiltration (CWI) with local analgesic is a promising adjunct to multimodal analgesia. However, its benefits in minimally invasive procedures and ERAS-adherent care remain unknown. This trial investigates whether the addition of CWI to standard ERAS care improves postoperative recovery following minimally invasive colorectal surgery. Methods In this single-centre, blinded, randomised controlled trial, 192 eligible patients are randomised to receive either a CWI system with bupivacaine 0.125% (the interventional arm), or a placebo CWI with physiological saline (the control arm). All patients receive standardized ERAS perioperative care with multimodal analgesia. The primary outcome is the Quality of Recovery-15 score (QoR-15NL) on postoperative day 2. Secondary outcomes include QoR-15NL and pain scores (postoperative days 1–5), opioid consumption, length of hospital stay, key functional recovery milestones, and 90-day postoperative complications. Discussion This will be the first randomised controlled trial evaluating the effect of CWI within minimally invasive and ERAS-adherent colorectal surgery. The trial findings may improve evidence-based perioperative care guidelines and enhance postoperative multimodal analgesia.